Conscious and unconscious memory differentially impact attention: Eye movements, visual search, and recognition processes - Ramey, Michelle M. (Cognition, 2019)
A hotly debated question is whether memory influences attention through conscious or unconscious processes. To address this controversy, we measured eye movements while participants searched repeated real-world scenes for embedded targets, and we assessed memory for each scene using confidence-based methods to isolate different states of subjective memory awareness. We found that memory-informed eye movements during visual search were predicted both by conscious recollection, which led to a highly precise first eye movement toward the remembered location, and by unconscious memory, which increased search efficiency by gradually directing the eyes toward the target throughout the search trial. In contrast, these eye movement measures were not influenced by familiarity-based memory (i.e., changes in subjective reports of memory strength). The results indicate that conscious recollection and unconscious memory can each play distinct and complementary roles in guiding attention to facilitate efficient extraction of visual information.